2021
DOI: 10.1108/qaoa-02-2021-0024
|View full text |Cite
|
Sign up to set email alerts
|

Living in a care home during COVID-19: a case study of one person living with dementia

Abstract: Purpose This paper aims to understand the lived experience of a person living with dementia in a care home during the COVID-19 pandemic. It responds to the absence in research of the voices of people with dementia living in care homes during the pandemic. Design/methodology/approach The paper adopts a single case study design applied thematic analysis to semi-structured interview data to discover the experiences of one person living with dementia in a care home during a period of lockdown. Findings Five th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…The full text of all 33 remaining potentially eligible studies were retrieved, and 15 papers were excluded with reasons, leaving 18 studies included. The studies were published in a range of countries including: Spain (3) (Cortés Zamora et al, 2022; Pereiro et al, 2021; Pérez‐Rodríguez et al, 2021), Turkey (2) (Arpacıoğlu et al, 2021; Savci et al, 2021), United Kingdom (1) (Davies‐Abbott et al, 2021), New Zealand (1) (Cheung et al, 2021), Israel (1) (Ayalon & Avidor, 2021), France (1) (El Haj et al, 2020), China (1) (Ho et al, 2022), Switzerland (1) (Huber & Seifert, 2022), Canada (1) (Ickert et al, 2021), Belgium (1) (Kaelen et al, 2021), United States of America (1) (Levere et al, 2021), Sweden (1) (Lood et al, 2021), Ireland (1) (Murphy et al, 2022), Croatia (1) (Solić et al, 2021), and Thailand (1) (Srifuengfung et al, 2021). All studies were conducted during the COVID‐19 pandemic from early 2020 to mid‐2021.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The full text of all 33 remaining potentially eligible studies were retrieved, and 15 papers were excluded with reasons, leaving 18 studies included. The studies were published in a range of countries including: Spain (3) (Cortés Zamora et al, 2022; Pereiro et al, 2021; Pérez‐Rodríguez et al, 2021), Turkey (2) (Arpacıoğlu et al, 2021; Savci et al, 2021), United Kingdom (1) (Davies‐Abbott et al, 2021), New Zealand (1) (Cheung et al, 2021), Israel (1) (Ayalon & Avidor, 2021), France (1) (El Haj et al, 2020), China (1) (Ho et al, 2022), Switzerland (1) (Huber & Seifert, 2022), Canada (1) (Ickert et al, 2021), Belgium (1) (Kaelen et al, 2021), United States of America (1) (Levere et al, 2021), Sweden (1) (Lood et al, 2021), Ireland (1) (Murphy et al, 2022), Croatia (1) (Solić et al, 2021), and Thailand (1) (Srifuengfung et al, 2021). All studies were conducted during the COVID‐19 pandemic from early 2020 to mid‐2021.…”
Section: Resultsmentioning
confidence: 99%
“…Qualitative findings from various countries revealed that the pandemic evoked feelings of depression, fear, anxiety, and loneliness. Residents reported feelings of sadness and frustration, many stated they were depressed (Ayalon & Avidor, 2021; Davies‐Abbott et al, 2021; Ickert et al, 2021; Kaelen et al, 2021).
I'm lonely here and sad, and as time goes on, its becoming, like there's a lot more people that's depressed, and I cry at night.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, further research is necessary to provide a stronger evidence base for the benefits of intergenerational practice and how to support children and adults who may find it more difficult to engage. New dialogic ways are needed to actively listen to the voices of young children and older adults in care to optimise opportunities for learning and development (Davies-Abbott et al, 2021 ; Murray, 2019 ). One way to address is taking a co-productive approach, doing research with [rather than on] children, older adults, practitioners to generate new knowledge and understandings (Clark, 2017 ).…”
Section: Discussionmentioning
confidence: 99%